Holy women of the Syrian Orient - Brock, Sebastian P.; Harvey, Susan Ashbrook (The Transformation of the classical heritage, 1998)
Mary, the niece of Abraham of Qidun -- Pelagia, of Antioch -- Persian martyrs -- Women martyrs of Najran -- From the Lives of the eastern saints / by John of Ephesus -- Anastasia -- Febronia -- Shirin